Effect of antimalarials on clinical outcomes in lupus nephritis - Peña-Vizcarra, Óscar R; Zavala-Miranda, María Fernanda; Juárez-Cuevas, Bernardo; Márquez-Macedo, Sofía E; Hernández-Andrade, Adriana; Nordmann-Gomes, Alberto; Pérez-Arias, Abril A; Morales-Buenrostro, Luis E; Mejía-Vilet, Juan M (Rheumatology (Oxford, England), 2024)
Objectives To evaluate the effect of antimalarial drugs in response to therapy, incidence of LN flares, and progression of kidney disease in a large LN cohort. Methods We retrospectively studied 424 biopsy-proven LN patients followed for >3 years. We obtained demographic, clinical, laboratory, histopathological and treatment variables. Antimalarial use was approached as (i) users vs no users, (ii) according to prevalent vs incident use regarding the LN flare and (iii) according to the type of antimalarial. All outcomes were evaluated by time-to-event analyses. Adjusted hazard ratios were obtained by Cox regression. Results The cohort included 424 patients, median age of 29 years (IQR 23–37), 96% female, with a median eGFR of 81 ml/min/1.73 m2 (IQR 48–118) and proteinuria of 3.4 g/g (IQR 1.9–5.5). Antimalarial use was associated with higher complete response (aHR 1.57, 1.08–2.27), lower incidence of kidney flares (aHR 0.63, 0.43–0.92) and lower progression to kidney failure (aHR 0.37, 0.23–0.53). The effect of antimalarials on these outcomes was modified by the presentation eGFR, histological class and/or concomitant initial immunosuppressor. These protective effects were observed in patients with prevalent or incident use regarding the LN flare and patients using hydroxychloroquine. The incidence of toxic retinopathy was 1.7%, 5.7% and 8.8% by 3, 5 and 7 years of continued antimalarial use, respectively. Conclusion The use of antimalarial drugs is associated with increased response to therapy, lower incidence of kidney flares, and lower progression to kidney failure in LN patients. Conversely, this population is at high risk of toxic maculopathy, and yearly ophthalmologic examination is recommended. Graphical abstract